Noninvasive PK11195‐PET Image Analysis Techniques Can Detect Abnormal Cerebral Microglial Activation in Parkinson's Disease. Issue 5 (4th May 2018) - Kang, Yeona; Mozley, P. David; Verma, Ajay; Schlyer, David; Henchcliffe, Claire; Gauthier, Susan A.; Chiao, Ping C.; He, Bin; Nikolopoulou, Anastasia; Logan, Jean; Sullivan, Jenna M.; Pryor, Kane O.; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Neuroinflammation has been implicated in the pathophysiology of Parkinson's disease (PD), which might be influenced by successful neuroprotective drugs. The uptake of [ 11 C](R)‐PK11195 (PK) is often considered to be a proxy for neuroinflammation, and can be quantified using the Logan graphical method with an image‐derived blood input function, or the Logan reference tissue model using automated reference region extraction. The purposes of this study were (1) to assess whether these noninvasive image analysis methods can discriminate between patients with PD and healthy volunteers (HVs), and (2) to establish the effect size that would be required to distinguish true drug‐induced changes from system variance in longitudinal trials. METHODS: The sample consisted of 20 participants with PD and 19 HVs. Two independent teams analyzed the data to compare the volume of distribution calculated using image‐derived input functions (IDIFs), and binding potentials calculated using the Logan reference region model. RESULTS: With all methods, the higher signal‐to‐background in patients resulted in lower variability and better repeatability than in controls. We were able to use noninvasive techniques showing significantly increased uptake of PK in multiple brain regions of participants with PD compared to HVs. CONCLUSION: Although not necessarily reflecting absolute values, these noninvasive image analysis methods can discriminate between PD patients and HVs. We see a difference of 24% in the substantia nigra between PD and HV with a repeatability coefficient of 13%, showing that it will be possible to estimate responses in longitudinal, within subject trials of novel neuroprotective drugs.